Beautiful Harmony : Political Project Behind Japan’s New Era Name - Kumada, Naoko (2019)
The shifting dynamics around the new era name (gengō 元号) offers an opportunity to understand how the domestic politics of the LDP’s project of ultranationalism is shaping a new Japan and a new form of nationalism.